Integrating Deep Learning and Augmented Reality in English as a Foreign Language Teaching (EFLT): a Literature Review - Astuti, Ruslina Tri (Jurnal Pendidikan Madrasah, 2025)
In recent years, both Deep Learning and Augmented Reality (AR) have emerged as transformative approaches in education, particularly in English as a Foreign Language Teaching (EFLT). However, a gap remains in synthesizing research that explores their combined pedagogical potential, especially in the context of developing countries such as Indonesia. This systematic literature review aims to examine the integration of Deep Learning and AR in EFLT, focusing on their roles in enhancing learner engagement, critical thinking, and language acquisition. Relevant peer-reviewed studies published between 2015 and 2024 were collected from databases such as Scopus, ERIC, and Google Scholar. The analysis identified recurring themes including AR's positive impact on student motivation and contextual understanding, and Deep Learning’s support for higher-order thinking and collaborative tasks. Challenges such as limited infrastructure, insufficient teacher training, and lack of localized content were also highlighted. The review concludes with recommendations for future research, including the need for culturally responsive AR tools, professional development for teachers, and longitudinal studies on learning outcomes. This synthesis offers practical and theoretical insights for educators, policymakers, and researchers aiming to innovate EFLT through technology integration.